FDA Public Workshop Summary—Coccidioidomycosis (Valley Fever): Considerations for Development of Antifungal Drugs. (15th October 2021) - O'Shaughnessy, Elizabeth; Yasinskaya, Yuliya; Dixon, Cheryl; Higgins, Karen; Moore, Jason; Reynolds, Kellie; Ampel, Neil M; Angulo, David; Blair, Janis E; Catanzaro, Antonino; Galgiani, John N; Garvey, Edward; et al.
Abstract: Coccidioidomycosis is a fungal disease endemic to the southwestern United States, Mexico, and Central and South America. Prevalence rates are increasing steadily, and new endemic areas of Coccidioides are emerging. Standard treatment is often administered for months to decades, and intolerance to medications and treatment failures are common. No new treatments for coccidioidomycosis have been approved in the United States in nearly 40 years. On 5 August 2020, the US Food and Drug Administration convened experts in coccidioidomycosis from academia, industry, patient groups, and other government agencies to discuss the disease landscape and strategies to facilitate product development for treatment of coccidioidomycosis. This article summarizes the key topics concerning drug development for coccidioidomycosis presented by speakers and panelists during the workshop, such as unmet need, trial designs, endpoints, incentives, research and development support, and collaborations to facilitate antifungal drug development. Abstract : There has been renewed interest in drug development for coccidioidomycosis. The US Food and Drug Administration (FDA) convened a public workshop on 5 August 2020 to discuss regulatory pathways, trial designs, and efforts to enhance drug development.